Novel deletion of exon 3 in TYR gene causing Oculocutaneous albinism 1B in an Indian family along with intellectual disability associated with chromosomal copy number variations - Somprakash Dhangar; Purvi Panchal; Jagdeeshwar Ghatanatti; Jitendra Suralkar; Anjali Shah; Babu Rao Vundinti (BMC, 2022)
Abstract Background Oculocutaneous albinism (OCA) is an autosomal recessive disorder characterized by hypo-pigmentation of skin, hair, and eyes. The OCA clinical presentation is due to a deficiency of melanin biosynthesis. Intellectual disability (ID) in OCA cases is a rare clinical presentation and appropriate diagnosis of ID is challenging through clinical examination. We report an Indian family with a rare co-inheritance of OCA1B and ID due to a novel TYR gene variant and chromosomal copy number variations. Methods We have done a study on three siblings (2 males and 1 female) of a family where all of them presented with hypopigmented skin, hair and eyes. The male children and their father was affected with ID. Targeted exome sequencing and multiplex ligation-dependent probe amplification analysis were carried out to identify the OCA1B and ID associated genomic changes. Further Array-CGH was performed using SurePrint G3 Human CGH + SNP, 8*60 K array. Results A rare homozygous deletion of exon 3 in TYR gene causing OCA1B was identified in all three children. The parents were found to be heterozygous carriers. The Array-CGH analysis revealed paternally inherited heterozygous deletion(1.9 MB) of 15q11.1-> 15q11.2 region in all three children. Additionally, paternally inherited heterozygous deletion(2.6 MB)of 10q23.2-> 10q23.31 region was identified in the first male child; this may be associated with ID as the father and the child both presented with ID. While the 2nd male child had a denovo duplication of 13q31.1-> 13q31.3 chromosomal region. Conclusion A rare homozygous TYR gene exon 3 deletion in the present study is the cause of OCA1B in all three children, and the additional copy number variations are associated with the ID. The study highlights the importance of combinational genetic approaches for diagnosing two different co-inherited disorders (OCA and ID). Hence, OCA cases with additional clinical presentation need to be studied in-depth forthe appropriate management of the disease.